Reference ranges for the linear dimensions of the intracranial ventricles in preterm neonates. Issue 3 (1st May 2000) - Davies, M W; Swaminathan, M; Chuang, S L; Betheras, F R
Abstract : AIMS: To establish normal ranges, in preterm infants < 33 weeks' gestation, for measurements of the lateral, third, and fourth ventricles and to assess intra-observer and inter-observer reliability. To assess the effect of head position during scanning on lateral ventricle size. To determine whether sex influences ventricle size. METHODS: A prospective study involving infants < 33 weeks' gestational age (GA) at birth. Cranial ultrasound scans were done during the first 3 days of life. Linear dimensions of the anterior horn width and thalamo-occipital distance of the lateral ventricles, the width of the third ventricle, and the width and length of the fourth ventricle were measured. Measurements were plotted against GA and reference ranges produced. All measurements were tested for intra-observer and inter-observer reliability. Head position and sex differences were studied. RESULTS: 120 infants with known GA (23 +1 to 32 +6 weeks) had their intracranial ventricles measured. Reference ranges obtained were—anterior horn width: 0–2.9 mm; thalamo-occipital distance: 8.7–24.7 mm; third ventricle width: 0–2.6 mm; fourth ventricle width: 3.3–7.4 mm; fourth ventricle length: 2.6–6.9 mm. Dependent and non-dependent lateral ventricles did not differ significantly in size. There was no clinically significant difference in ventricular size between sexes. CONCLUSIONS: Reference ranges for the measurement of the intracranial ventricles in preterm infants from 23 to 33 weeks' GA are provided and can be used in the diagnosis and assessment of ventricular enlargement in preterm infants. All measurements have good intra-observer and inter-observer reliability. Head position at the time of scanning does not influence the asymmetry of the lateral ventricular measurements. The infant's sex does not influence ventricular size.